O PAPEL DO COORDENADOR PEDAGÓGICO EM DIFERENTES CONTEXTOS - Santos David, Ricardo (LINKSCIENCEPLACE, 2026)
The purpose of this literature review is to evaluate between ideal and real experiences in the school environment. The paper aims to identify the duties of the school coordinator within the school from the legislation, and reflect through data, contributing and building an identity as overcoming the challenges before traverses’ in school life. The researches provides a conceptual overview of the legislation then the reality of the role of the school coordinator, and confirm the hypothesis of the school coordinator is currently performing bureaucratic functions, leaving aside his true role in the school, with teachers teaching support. Presenting suggestions to engineer’s supervisors and teachers to plan their lessons.